Agronomic and Yield Potentials of Bambara Groundnut (Vigna Subterranea (L.)Verdc.) in Northeastern Nigeria - Tyoakoso, M. M.; Jakusko, B. B.; Anayib, M.; Abdu, I. (ՀԱԱՀ հիմնադրամ)
Field trials were conducted in 2015 rainy season on the Teaching and Research Farm of the Department of Crop Production and Horticulture, Modibbo Adama University of Technology, Yola and Department of Crop Science, Taraba State College of Agriculture, Jalingo to investigate the effect of inter-row spacing and nitrogen rates on the growth and yield of Bambara groundnut (Vigna subterranean L.). The experiments were laid out in a split-plot design with three nitrogen rates, 20 kgNha-1, 25 kgNha-1 and 30 kgNha-1 as main plot treatments and four inter-row spacing of 20 cm, 25 cm, 30 cm and 35 cm as the sub plot treatment. Data were collected on the growth and yield parameters and were subjected to Analysis of Variance (ANOVA) and Least Significant Difference (LSD) procedure. Due to the findings it is suggested that nitrogen rate of 20kgNha-1 and inter-row spacing of 35 cm should be adopted.
Keywords: Agronomy and Agroecology